2019
DOI: 10.3390/ijms20071625
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Water-Borne Polyurethane Nanofibrous Membrane as a Barrier for Preventing Postoperative Peritendinous Adhesion

Abstract: Peritendinous adhesion is a major complication after tendon injury and the subsequent repairs or reconstructions. The degree of adhesion can be reduced by the interposition of a membranous barrier between the traumatized tendon and the surrounding tissue. In the present study, electrospun water-borne polyurethane (WPU) nanofibrous membranes (NFMs) were created for use after the reparation or reconstruction of tendons to reduce adhesion. In the electrospinning process, water was employed as the solvent for WPU,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
(59 reference statements)
0
15
1
2
Order By: Relevance
“…Electrospinning has become a widely applied method to fabricate nanofibers due to its cost-effectiveness, simplicity, and suitability for mass production ( Xue et al, 2019 ; Keshvardoostchokami et al, 2020 ; Xu et al, 2021 ). Owing to its dense fibrous structure, tiny pore size, controllable mechanical properties, and adjustable degradation rate, the electrospun nanofibrous membrane has shown great potential in preventing postoperative adhesions as a physical barrier ( Chen et al, 2019 ; Alimohammadi et al, 2020 ; Mao et al, 2021 ). In our pilot study, we have discovered the elelctrospun GT/PCL (mass ratio 50:50) nanofibrous membrane might become a promising barrier to prevent postoperative cardiac adhesion ( Feng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning has become a widely applied method to fabricate nanofibers due to its cost-effectiveness, simplicity, and suitability for mass production ( Xue et al, 2019 ; Keshvardoostchokami et al, 2020 ; Xu et al, 2021 ). Owing to its dense fibrous structure, tiny pore size, controllable mechanical properties, and adjustable degradation rate, the electrospun nanofibrous membrane has shown great potential in preventing postoperative adhesions as a physical barrier ( Chen et al, 2019 ; Alimohammadi et al, 2020 ; Mao et al, 2021 ). In our pilot study, we have discovered the elelctrospun GT/PCL (mass ratio 50:50) nanofibrous membrane might become a promising barrier to prevent postoperative cardiac adhesion ( Feng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This drastic reduction in the number of cells that penetrated an NFM in vitro also suggested its efficacy to prevent tendon adhesion in vivo due to the extrinsic fibroblastic cells. Indeed, the dense fiber morphology and the macroporous structure of the NFM shown in Figure 1 facilitates its use as a physical barrier to prevent postoperative adhesion [40]. That the number of penetrated cells of HAI40FB was significantly higher than HAI20FB may be due to the difference in pore sizes of the membrane [41].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, controlling inflammation and regulating cell growth, alignment, and components is important in the tendon regeneration field. Previous studies have shown the effectiveness and practical use of water-borne polyurethane nanofibrous membranous materials and other materials as barriers to reduce the degree of peritendinous adhesion in a rabbit model under safety [43,44]. On the other aspect of restoring the components and mechanical properties of injured tendons, there are still limited studies that report approaches that promote tissue regeneration, making tendon tissue regeneration a challenge in current therapeutic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical strength is an indicator of tendon healing and functional outcomes [43,44,60,61]. A recent study showed improved biomechanical properties in a repaired rotator cuff model with treatment with exosome-embedded fibrin sealant [62].…”
Section: Evs Have Been Generally Accepted As a Modality Of Cell-to-cell Communication Formentioning
confidence: 99%